2019
DOI: 10.1103/physrevc.100.035801
|View full text |Cite
|
Sign up to set email alerts
|

Role of the symmetry energy and the neutron-matter stiffness on the tidal deformability of a neutron star with unified equations of state

Abstract: The role of the symmetry energy and the neutron-matter stiffness on the tidal deformability of a cold nonaccreted neutron star is studied using a set of unified equations of state. Based on the nuclear energy-density functional theory, these equations of state provide a thermodynamically consistent treatment of all regions of the star and were calculated using functionals that were precision fitted to experimental and theoretical nuclear data. Predictions are compared to constraints inferred from the recent de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 105 publications
12
38
1
Order By: Relevance
“…As previously shown in Ref. [14], the unified EoS based on BSk24 is consistent with this constraint. From the formula obtained in Ref.…”
Section: A Approximate Analytic Solutionsupporting
confidence: 88%
See 1 more Smart Citation
“…As previously shown in Ref. [14], the unified EoS based on BSk24 is consistent with this constraint. From the formula obtained in Ref.…”
Section: A Approximate Analytic Solutionsupporting
confidence: 88%
“…The underlying functional was precision fitted to a large set of experimental and theoretical nuclear data [13]. We have recently shown that this unified EoS is also consistent with the various constraints inferred from the analyses of the gravitational and electromagnetic observations of GW170817 [14]. To better assess the importance of the crust, results for the Love number k 2 and the tidal deformability parameter Λ are compared in Section III to those obtained using the EoS of a purely liquid putative NS made entirely of homogeneous matter calculated with the same functional BSk24.…”
Section: Introductionsupporting
confidence: 56%
“…1 of Ref. [43], these functionals remain consistent with more recent ab initio calculations. All functionals are also consistent with EoS constraints inferred from heavy-ion collisions [59,75] and with various empirical determinations of the symmetry energy at densities n n 0 (see Fig.…”
Section: A Unified Equations Of State Of Dense Matter In Neutron Starssupporting
confidence: 88%
“…2 of Ref. [43]). The functionals mainly differ in their predictions for the density dependence of the symmetry energy at higher densities.…”
Section: A Unified Equations Of State Of Dense Matter In Neutron Starsmentioning
confidence: 88%
See 1 more Smart Citation